The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1083/jcb.143.5.1239
|View full text |Cite
|
Sign up to set email alerts
|

The “8-kD” Cytoplasmic Dynein Light Chain Is Required for Nuclear Migration and for Dynein Heavy Chain Localization in Aspergillus nidulans

Abstract: The heavy chain of cytoplasmic dynein is required for nuclear migration in Aspergillus nidulans and other fungi. Here we report on a new gene required for nuclear migration, nudG, which encodes a homologue of the “8-kD” cytoplasmic dynein light chain (CDLC). We demonstrate that the temperature sensitive nudG8 mutation inhibits nuclear migration and growth at restrictive temperature. This mutation also inhibits asexual and sexual sporulation, decreases the intracellular concentration of the nudG CDLC protein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 71 publications
(96 reference statements)
1
73
0
Order By: Relevance
“…The Aspergillus orthologue of LIS1, NUDF, 145 functions within a complex of NUD proteins, including NUDA (dynein heavy chain), NUDG (dynein light chain), NUDK (dynactin subunit Arp1) and NUDE. [145][146][147][148][149] The composition of this complex is conserved in mammals, demonstrating that nuclear positioning is an indispensable function. Aspergillus NUDE has two mammalian orthologues termed NUDE and NUDE-like (NDE1 and NDEL1), which interact with LIS1.…”
Section: Lis1 Ndel1 Nde1 and Disc1mentioning
confidence: 99%
“…The Aspergillus orthologue of LIS1, NUDF, 145 functions within a complex of NUD proteins, including NUDA (dynein heavy chain), NUDG (dynein light chain), NUDK (dynactin subunit Arp1) and NUDE. [145][146][147][148][149] The composition of this complex is conserved in mammals, demonstrating that nuclear positioning is an indispensable function. Aspergillus NUDE has two mammalian orthologues termed NUDE and NUDE-like (NDE1 and NDEL1), which interact with LIS1.…”
Section: Lis1 Ndel1 Nde1 and Disc1mentioning
confidence: 99%
“…16 Several of the nud genes (nudA, nudI and nudG) are subunits of cytoplasmic dynein, a microtubule-based motor protein, and nudK is a part of the dynein regulatory complex dynactin. [17][18][19] Recently, it has been shown that the Aspergillus nidulans cytoplasmic dynein heavy chain and NUDF localize to microtubule ends. 20 Furthermore, microtubules of nudA and nudF loss-of-function mutants were less dynamic; They showed a lower frequency of microtubule catastrophe events, a lower rate of shrinkage during catastrophe, and a lower frequency of rescue.…”
Section: Lis1 and Microtubule Regulationmentioning
confidence: 99%
“…In addition, cytoplasmic dynein is shown to move isolated nuclei along the astral microtubules in a cell free system (Reinsch and Karsenti, 1997) and facilitate nuclear fusion after fertilization in vivo (Payne et al, 2003). Although DLC1 is an integral component of the cytoplasmic dynein complex and its homologue plays a key role in both dynein localization and nuclear migration processes in Aspergillus (Beckwith et al, 1998), its role in nuclear positioning process was unknown in higher eukaryotes.…”
Section: Dlc1 Regulates Dynein-dynactin Function Involved In Nuclear mentioning
confidence: 99%